IMPACT OF AUDIT QUALITY ON EARNINGS MANAGEMENT OF CONSUMER GOODS FIRMS IN NIGERIA - Sirajo Bappah; Awwal Saad; Saidu Adamu; Shehu Usman Hassan (Gusau Journal of Accounting and Finance, 2024)
This study examines the impact of audit quality on earnings management of listed consumer goods firms in Nigeria. The study adopted correlational research design. The population of the covers all twenty-one (21) listed consumer goods firm in Nigeria and two-stages filter was used to arrive at a sample size of fifteen (15) consumer goods firms listed the floor of Nigerian Exchange group as at 31st December, 2022, the data were extracted from annual reports and accounts of the sampled firms for the period of ten (10) years from 2013-2022. Multiple regression was used as a technique of data analysis, regression result shows that audit reporting lag, audit client’s importance and auditor independence have a positive and significant impact on earnings management of the sampled firms, while auditor’s tenure has a negative and significant impact on earnings management. Based on the findings, the study concluded that audit reporting lag, audit client’s importance and auditor independence enhanced the earnings management. while, auditor tenure does not affect earnings management. Based on findings and conclusion, it is therefore, recommends that the regulatory bodies such as Financial Reporting Council of Nigeria and Security and Exchange Commission in Nigeria should ensure that audited reports for private companies are release within a regulated period, this is because prolonged audit lagged increase earnings management by giving management of the companies enough time to manipulate earnings. This will impede the users of financial information to take an informed decision.